SAT0088 Identification of Patients at High Risk for Death in Rheumatic Disease. (23rd January 2014) - Kleinert, S.; Breunig, M.; Tony, H.-P.; Feuchtenberger, M.; Kneitz, C.; Lehmann, S.; Angermann, C. E.; Ertl, G.; Störk, S.
Abstract : Background: Patients with rheumatic diseases (RD) have an increased mortality risk compared to the normal population, mainly due to cardiovascular (CV) disease. Only a proportion of this risk increase seems explained by traditional cardiovascular risk factors. It is therefore difficult to identify patients with RD at high risk. Objectives: We aimed to identify high risk patients for CV diseases and mortality by a screening program that is suitable for clinical practice in rheumatology. Methods: 612 consecutive patients attending the rheumatology outpatient department of the University Hospital underwent a comprehensive CV risk assessment including history taking, patient questionnaires, ECG, and laboratory measurements including natriuretic peptides (NTproBNP). Screening was regarded positive if any of the following was present: European CV disease risk assessment Score (SCORE) ≥3% or NTproBNP≥200 pg/ml or any pathological ECG pattern. Results: The patient population comprised patients with rheumatoid arthritis (RA, n=359) or various systemic autoimmune diseases (SAID, n=253) including connective tissue disease (n=157) and vasculitis (n=32). SCORE was ≥3% in 31%, 20% of the patients had a NTproBNP level ≥200 pg/ml, and 16% had a pathological ECG. Patients were followed for a median of 5.5 years. The figure shows KM-plots for the 3 screening strategies, and unadjusted hazard ratios with 95%CI. In an age- and sex-adjusted multivariable model, only NTproBNP≥200 pg/ml conferred independent prognostic information with HR 2.4 (1.10-5.39, P=0.028) and an area under the ROC curve of 82%. Image/graph: Conclusions: RD patients at high risk for death can be identified using simple screening tools. Particularly, patients with a SCORE ≥3% or NTproBNP ≥200 pg/ml are at high risk for death, justifying further diagnostics and closer long-term follow-up. Disclosure of Interest: None Declared